Review of Michael P. Krom, Justice and Charity: An Introduction to Aquinas’s Moral, Economic, and Political Thought - R. Jared Staudt (Journal of Moral Theology)
A review of Michael P. Krom, _Justice and Charity: An Introduction to Aquinas’s Moral, Economic, and Political Thought_